(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2021)
This article discusses the results of research work on the creation of biocapsules containing the optimal amount of environmentally friendly man-made waste needed to stimulate the growth of agricultural plants, their impact on soil fertility. In the course of scientific research, methods of chemical analysis were used to determine the pollutants contained in the soil, the method of pressing in the production of biocapsules, methods of detoxification and soil purification. For the manufacture of biocapsules from man-made waste, processed products were obtained, that is, biohumus, waste from the production of forest products – wood chips, limestone, and the remains of a clay deposit – clay lump. The use of biocapsules with a clear volume content of components-led to economic efficiency in saving fertilizers, did not pose a threat to the environment and the purity of products. When sowing seedlings on biocapsules, conditions are created that positively affect their yield. In all the biocapsule use cases in all the plants studied, the high product gain was observed to increase by 90 percent. According to the results of the study, it was proved that biocapsules do not show any inverse indicators of soil fertility. In the future, recommendations were developed for the acclimatization of various plants through biocapsules to local regions. The created biocapsules can be used not only in agricultural institutions, but also in the improvement of parks, various public places and courtyards of state buildings. Key words: biocapsule, growth stimulation, technogenic waste, secondary use of waste, agricultural plants, soil fertili.